O-039 Mechanical treatment of intracranial vasospasm using the comaneci device: multicenter experience. (23rd July 2022) - Salem, M; Khalife, J; Desai, S; Sharashidze, V; Badger, C; Luisa Kuhn, A; Monteiro, A; Siddiqui, A; Levy, E; Thomas, A; Lang, M; Burkhardt, J; et al.
Abstract : Introduction: We report large multicenter experience utilizing the Comaneci device (Rapid Medical, Yokneam, Israel) for endovascular treatment of medically-refractory intracranial vasospasm. Methods: Series of consecutive patients undergoing Comaneci mechanical dilatation for intracranial vasospasm, regardless of etiology, were extracted from prospectively-maintained registries in 7 North-American cerebrovascular centers (2019–2021). Intra-arterial vasodilators were allowed, with Comaneci device only utilized after absence of vessel dilation post-infusion. Pre- and post-vasospasm treatment scores were recorded for each treated segment, with primary outcome of radiological improvement in vasospasm score post-treatment. The primary clinical outcome was device safety profile and procedural device-related complications, with secondary endpoints of functional outcomes at last available follow-up. Results: 29 patients undergoing endovascular vasospasm treatment utilizing Comaneci device (median age 53; 69% females). Aneurysmal subarachnoid hemorrhage was the most common etiology of vasospasm (82.8%), with 65.5% of dilation procedures performed utilizing Comaneci-17 device and 89% of patients receiving intra-arterial vasodilators. The most treated segments were the anterior cerebral artery (40.4%) followed by middle cerebral artery (29.8%). A total 94 vessels received mechanical dilation; 74 of which had pre-treatment severe to critical vasospasm scores (i.e., vasospasm score of 3 or 4). Significant vasospasm drop defined as change from pre-treatment score of (3–4) to post-treatment of (0–2) was achieved in 89.2% of the cases, with 94.7% of the vessels (89 of 94) experiencing at least 1-point drop in vasospasm severity post- treatment. There were no major procedural or post-procedural device-related complications (i.e., vessel rupture/dissection or post-procedure intracerebral hemorrhage, etc.) encountered in any of the patients. Primary treatment failure (i.e., vessel unresponsive to treatment) was encountered in 1 vessel in 1 patient (1/94; 1.1%) while secondary treatment failure (i.e., vasospasm recurrence in previously treated segment requiring retreatment in another procedure) was noted in 16 vessels in 7 patients (16/94; 17%), with median time-to-retreatment of 2 days. Favorable clinical outcome of modified Rankin Scale score of 0–2 was noted in 52% of the patients over a median of 6 months of clinical follow-up. Conclusion': The Comaneci device provides a feasible complimentary strategy for endovascular treatment of refractory intracranial vasospasm with reasonable efficacy and favorable safety profile. Future prospective trials are warranted for further investigation. Disclosures: M. Salem: None. J. Khalife: None. S. Desai: None. V. Sharashidze: None. C. Badger: None. A. Luisa Kuhn: None. A. Monteiro: None. A. Siddiqui: None. E. Levy: None. A. Thomas: None. M. Lang: None. J. Burkhardt: None. A. Puri: None. B. Gross: None. E. Nossek: None. A. Hassan: None. H. Shaikh: None. B. Jankowitz: None.